2016
DOI: 10.4103/0019-557x.195853
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of suicide among patients admitted with suicide attempt in Tata main hospital, Jamshedpur

Abstract: The early identification and treatment of vulnerable populations with risk factors for suicide across the lifespan will help in planning and implementing strategies for prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 2 publications
2
20
0
Order By: Relevance
“…Alcohol/substance dependence was found in 4 subjects, that is, 8.6%, this finding is like the NCRB data (2020)[ 6 ] which showed that 6% of sample were dependent on substance/alcohol. Studies have shown that substance use independently increases the risk of suicidal behavior.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Alcohol/substance dependence was found in 4 subjects, that is, 8.6%, this finding is like the NCRB data (2020)[ 6 ] which showed that 6% of sample were dependent on substance/alcohol. Studies have shown that substance use independently increases the risk of suicidal behavior.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, in India, the 15–24 years age group has the highest suicide rate,[ 6 7 ] a finding consistent with the global trend. [ 8 ] Higher suicidality in this age group has been attributed to developmental changes, the significant influence of the psychological and socio-environmental factors, coupled with the prominence of impulsivity, indulgence in substance use, and acquired capability to bear the pain and fear associated with suicide and ability to execute the suicidal plans.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Four studies examining humiliation [ 68 71 ] scored 50% or less in the current methodological quality assessment, indicating high-risk of bias in the data reviewed. Notably, poor scores were attributed to JBI Checklist items such as valid exposure measures, identification of confounding factors, or strategies to deal with the confounding factors (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zinki et al also exhibited a steady trend of suicide in Australia [11]. Maybe one of the reasons for the increasing trend is related to improving the registration system, increasing drug abuse, unemployment in high-incidence provinces, increasing depression, political issues such as sanctions, and economic problems such as uctuating in ation in the country [12,13].…”
Section: Discussionmentioning
confidence: 99%